Pengaruh Kompensasi, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan PT. Matahari Department Store Cabang Festival Citylink - Andini, Fitriyani; Wijaya, Fanji; Ismail, Gurawan Dayona (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
PT Matahari Department Store ranked first in the retail business in Indonesia in 2023. However, based on a pre-research study conducted by researchers on 20 employees of PT Matahari Department Store Festival Citylink Branch, it was found that there was a gap phenomenon in the company related to employee compensation, motivation, and work discipline. So, this research aims to analyze the influence of compensation, work motivation, and work discipline on performance. This research involved a sample of 100 employees. This research found that compensation partially impacts employee performance, but work motivation and discipline do not. The result also found that compensation, work motivation, and work discipline significantly impact employee performance